Building websites with VB.NET and DotNetNuke 3.0 - Egan, Daniel N.; Safari eBooks (Birmingham, U.K. : Packt Pub., 2005)
"If you work with ASP.NET and VB.NET, and want an interactive website, with forums, news and image management, where visitors can register, participate and contribute to your site, then DotNetNuke is the ideal solution for you. This book is your indispensable guide to creating content-rich websites with DotNetNuke 3.0, as quickly as possible. The first part of this book gives you a deep understanding of working with basic DotNetNuke sites, guiding you through the features and giving you the confidence to create and manage your own site. After that, you will journey to the heart of DotNetNuke, and learn about its core architecture. From there, you will learn how to customize DotNetNuke sites through skinning and creating custom modules."--Resource description page.
Description based on print version record.
"A practical guide to creating and maintaining your own website with DotNetNuke, the free, open-source evolution of Microsoft's IBuySpy Portal"--Cover.
Include index.
Keywords: Microsoft Visual BASIC; Active server pages; Web portals -- Design; Microsoft .NET.; Internet programming; Web sites -- Design; Electronic books